A One-Pot Tandem Approach for the Synthesis of 5-(Het)aryloxazoles from Substituted (Het)aryl Methyl Alcohols and Benzyl Bromides - Vinay Kumar, Koravangala S.; Swaroop, Toreshettahally R.; Rajeev, Narasimhamurthy; Vinayaka, Ajjampura C.; Lingaraju, Gejjalagere S.; Rangappa, Kanchugarakoppal S.; Sadashiva, Maralinganadoddi P. (Synlett, 2016)
A new modified van Leusen strategy has been developed for the synthesis of biologically significant 5-substituted oxazoles by the reaction of (het)aryl methyl alcohols or benzyl bromides as precursors with tosylmethylisocyanide (TosMIC) under basic conditions. This method is efficient, takes place under mild reaction conditions, and is tolerant of various functional groups with high yield.
Keywords: oxazole; TosMIC; T3P®; DMSO; NaHCO3